Covid-19 Outbreak Impact on Sectoral Firm Performance Listed in Indonesia Stock Exchange in Various Sectors - Natara Devi Anafia; Maria Ulpah (IQTISHADUNA, 2021)
The goal of this research is to estimate the impact of the Covid-19 outbreak on firm performance in Indonesia on a sectoral level. According to BPS data (2020), Indonesia's GDP fell in Q2 and Q3 2020, even falling to a negative level. The drop in GDP, on the other hand, was not homogenous across all sectors. In Q2 and Q3 2020, there are sectors with positive GDP and sectors with negative GDP. This research looks at three sectors with positive GDP and three with negative GDP. This research uses secondary data, namely financial report data published by each of the firms. STATA software was used to process research data using panel data regression. This research provides results that the Covid-19 outbreak had a positive impact on firm performance in sectors with positive GDP growth during the outbreak and a negative impact on firm performance in sectors with negative GDP growth during the outbreak. As sectorally, the Covid-19 outbreak had a positive impact on firm performance in the health sector. The Covid-19 outbreak had a negative impact on firm performance in several sectors, these are the transportation and logistic sector, car and motorcycle trading sector, and the construction sector.